Kontribusi Ekonomi Kreatif Dalam Mendukung Sektor Pariwisata Di Kabupaten Sikka - Bertholomeus Baghi Tjeme (Jurnal Transformasi Bisnis Digital, 2024)
Sikka Regency is an area with superior tourism potential but the contribution of the tourism sector does not have a significant influence on economic growth, this is due to the low contribution of the creative economy in supporting the tourism sector which is influenced by less attractive and competitive creative economy products, lack of promotion and branding, lack of collaboration and partnership between tourism actors and creative economy actors and lack of support from the government and related institutions. To overcome these problems, the proposed solution is the existence of regulations as a strong legal foundation and framework for policies and programs that support the creative economy in Sikka Regency. The writing of this Policy Paper aims to enable the creative economy to contribute more to the development of the tourism sector in Sikka Regency and increase regional economic growth as well as policy recommendations to overcome the low contribution of the creative economy to support tourism in Sikka Regency. The method used in this paper is problem tree analysis involving literature study, field observation and in-depth interviews with tourism and creative economy actors. The recommended policy option is a Sikka Regent Regulation on Creative Economy that can provide a legal framework and programs that support the development of the creative economy sector in Sikka Regency.